(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2013)
I expose my teaching experience as a Human Development Research Professor within the 3rd semester Human Development undergraduate program. It includes 2 aspects, first: a description of strategies used for the learning of qualitative research methods through fieldworks. These involve social organizations like: social movements, organized groups promoting wellness, community networks, etc. Secondly, I interpret a systematization of 4o and 5o semester approved students; a survey was used. It was organized taking into account 3 topics: main learning obtained, obstacles students find, and suggestions to improve didactics strategies used in the classroom. Such information has shown how accurate these strategies are, like presentations made by research methods study groups, open discussions about published researches, difficulties students find on observing and interviewing communi ties’ daily life and finally how important the career is for its students.